Comparison of Internal Fixations for Distal Clavicular Fractures Based on Loading Tests and Finite Element Analyses - Rina Sakai; Terumasa Matsuura; Kensei Tanaka; Kentaro Uchida; Masaki Nakao; Kiyoshi Mabuchi (The Scientific World Journal)
It is difficult to apply strong and stable internal fixation to a fracture of the distal end of the clavicle because it is unstable, the distal clavicle fragment is small, and the fractured region is near the acromioclavicular joint. In this study, to identify a superior internal fixation method for unstable distal clavicular fracture, we compared three types of internal fixation (tension band wiring, scorpion, and LCP clavicle hook plate). Firstly, loading tests were performed, in which fixations were evaluated using bending stiffness and torsional stiffness as indices, followed by finite element analysis to evaluate fixability using the stress and strain as indices. The bending and torsional stiffness were significantly higher in the artificial clavicles fixed with the two types of plate than in that fixed by tension band wiring (P<0.05). No marked stress concentration on the clavicle was noted in the scorpion because the arm plate did not interfere with the acromioclavicular joint, suggesting that favorable shoulder joint function can be achieved. The stability of fixation with the LCP clavicle hook plate and the scorpion was similar, and plate fixations were stronger than fixation by tension band wiring.